After-hours physician care for patients with do-not-resuscitate orders: An observational cohort study. (March 2014) - Hsu, Nin-Chieh; Chang, Ray-E; Tsai, Hung-Bin; Lin, Yu-Feng; Shu, Chin-Chung; Ko, Wen-Je; Yu, Chong-Jen
Background: Medical care at night for patients with do-not-resuscitate orders and the practice patterns of the on-call residents have rarely been reported. Aim: To evaluate the after-hours physician care for patients with do-not-resuscitate orders in the general medicine ward. Design: Observational study. Setting/participants: This study was conducted at an urban, university-affiliated academic medical center in Taiwan. The night shift nurses consecutively recorded every event that required calling the duty residents. Patients with and without a do-not-resuscitate order were compared in demographics, reasons for calling, residents' response, and nurses' satisfaction. A standard report form was established for the nurses to record events. Results: From October 2009 to September 2010, 1379 inpatients contributed to 456 after-hours calls. do-not-resuscitate patients accounted for 256 (18.7%) of all inpatients, and 160 (35.1%) of all after-hours calls. The leading reason for calls was abnormal vital signs, which was significantly higher for patients with do-not-resuscitate orders compared to patients without a do-not-resuscitate order (64.4% vs 36.1%, p < 0.001). The pattern of residents' responses showed a significant difference with more bedside visits for patients with do-not-resuscitate orders ( p < 0.001). The nurses were usually satisfied with the residents' management of both groups. Conclusion: Abnormal vital sign, rather than symptom, was the leading reason for after-hours calls. The existence of do-not-resuscitate order produced different medical needs and physician workload. Patients with do-not-resuscitate orders accounted for one-third of night calls and nearly half of bedside visits by on-call residents and may require a different care approach.